Endoscopic full thickness resection in the colo-rectum: outcomes from the UK Registry. Issue 6 (June 2021) - Boger, Philip; Rahman, Imdadur; Hu, Maxworth; Ayaru, Laksh; Bhandari, Pradeep; Chedgy, Fergus; Green, Susi; Hayat, Mumtaz; Hopper, Andrew D.; Ishaq, Sauid; Martin, John; McCallum, Iain; et al.
Abstract : Background: Endoscopic full-thickness resection (eFTR) of the colon using the full-thickness resection device (FTRD) is a novel method for removing lesions involving, or tethered to, deeper layers of the colonic wall. The UK FTRD Registry collected data from multiple centres performing this procedure. We describe the technical feasibility, safety and early outcomes of this technique in the UK. Methods: Data were collected and analysed on 68 patients who underwent eFTR at 11 UK centres from April 2015 to June 2019. Outcome measures were technical success, procedural time, specimen size, R0 resection, endoscopic clearance, and adverse events. Reported technical difficulties were collated. Results: Indications for eFTR included non-lifting polyps (29 cases), T1 tumour resection (13), subepithelial tumour (9), and polyps at the appendix base or diverticulum (17). Target lesion resection was achieved in 60/68 (88.2%). Median specimen size was 21.7 mm (10–35 mm). Histologically confirmed R0 resection was achieved in 43/56 (76.8%) with full-thickness resection in 52/56 (92.9%). Technical difficulties occurred in 17/68 (25%) and complications in 3/68 (5.9%) patients. Conclusion: eFTR is a useful technique with a high success rate in treating lesions not previously amenable to endoscopic therapy. Whilst technical difficulties may arise, complication rates are low and outcomes are acceptable, making eFTR a viable alternative to surgery for some specific lesions.